Validation of Doi’s weighted average glucose as a measure of post-load glucose excursion for clinical use - Saif Badran; Suhail Doi; Atalla Hammouda; Omran Musa; Abdella Habib (Biomolecules & Biomedicine, 2023)
In this study, we examined the performance of a novel index of glucose excursion (Doi’s weighted average glucose [dwAG]) in relation to the conventional measure of area under the oral glucose tolerance test (A-GTT) and the homeostatic model assessment for insulin sensitivity (HOMA-S) and pancreatic beta cell function (HOMA-B). A cross-sectional comparison of the new index was conducted using 66 oral glucose tolerance tests (GTTs) performed at different follow-up times among 27 participants who had undergone surgical subcutaneous fat removal (SSFR). Comparisons across categories were made using box plots and the Kruskal-Wallis one-way ANOVA on ranks. Passing-Bablok regression was used to compare the dwAG against the conventional A-GTT. The Passing-Bablok regression model suggested a cutoff for normality for the A-GTT of 15.14 mmol/L·2h-1 compared to the dwAG’s suggested threshold of 6.8 mmol/L. For every 1 mmol/L·2h-1 increase in A-GTT, the dwAG value increased by 0.473 mmol/L. The glucose area under the curve correlated well with the four defined dwAG categories, with at least one of the categories having a different median A-GTT value (KW Chi2 = 52.8 [df = 3], P < 0.001). The HOMA-S tertiles were also associated with significantly different levels of glucose excursion measured through both the dwAG value (KW Chi2 = 11.4 [df = 2], P = 0.003) and A-GTT measure (KW Chi2 = 13.1 [df = 2], P = 0.001). It is concluded that the dwAG value and categories serve as a simple and accurate tool that can be used for interpreting glucose homeostasis across clinical settings.